2018
DOI: 10.1097/bot.0000000000001134
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Supracondylar Humerus Fractures: Does After-Hours Treatment Influence Outcomes?

Abstract: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…All six articles articles retrospectively compared postoperative outcomes of pediatric patients who had surgery for supracondylar humerus fractures at different times of the day. Primary outcomes in the studies were reduction quality [ 14 , 15 , 16 , 17 , 18 , 19 ], malunion rate [ 15 ], loss of reduction [ 17 ] and complications [ 16 ]. Also, functional outcomes in follow-up were assessed in three articles [ 14 , 15 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…All six articles articles retrospectively compared postoperative outcomes of pediatric patients who had surgery for supracondylar humerus fractures at different times of the day. Primary outcomes in the studies were reduction quality [ 14 , 15 , 16 , 17 , 18 , 19 ], malunion rate [ 15 ], loss of reduction [ 17 ] and complications [ 16 ]. Also, functional outcomes in follow-up were assessed in three articles [ 14 , 15 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Paci et al investigated the results of SHFs operated during working or non-working hours. They reported no difference in terms of operative duration and outcomes, however mal-union rate was higher in patients operated at night in non-working hours (7). Yıldırım et al reported similar reduction quality in pediatric SHFs who were operated in the same or next day of their admission.…”
Section: Discussionmentioning
confidence: 96%
“…Operating the pediatric SHF patients within working or non-working hours is still debating in the literature. In recent studies, mal-union rates were reported to be higher in pediatric SHFs operated in the night hour surgeries and mean operative duration was found to be shorter in daytime surgeries (7,8). On the other hand, in a recent article, there was no difference in reduction quality, complications and outcomes between pediatric SHF patients operated during the night or the daytime (9).…”
Section: Introductionmentioning
confidence: 99%
“…Paci et al investigated the results of SHFs operated during working or non-working hours. They reported no difference in terms of operative duration and outcomes, however, mal-union rate was higher in patients operated at night in non-working hours [ 6 ]. Yıldırım et al reported similar reduction quality in pediatric SHFs who were operated in the same or next day of their admission.…”
Section: Discussionmentioning
confidence: 99%
“…Operating the pediatric SHF patients within working or non-working hours is still debating in the literature. In recent studies, mal-union rates were reported to be higher in pediatric SHFs operated in the night hour surgeries and mean operative duration was found to be shorter in daytime surgeries [ 6 , 7 ]. On the other hand, in a recent article, there was no difference in reduction quality, complications and outcomes between pediatric SHF patients operated during the night or the daytime [ 8 ].…”
Section: Introductionmentioning
confidence: 99%